The Regulation of employment agreements after the enactment of law number 11 of 2020 concerning job Creation (Research, Society and Development, 2022)
The passage of legislation of Law Number 11 of 2020 concerning Job Creation will affect changes to the regulation regarding employment, considering that it is in Law Number 11 of 2020 concerning Job Creation. So far, the issue of increasing investment in order to attract investors to invest in Indonesia by creating job opportunities is the opposite side of protecting workers' rights and improving workers' welfare. It is expected that the job copyright law can accommodate the interests of investors and workers. The government considers that the Job copyright law is an attempt by the government to create a middle way to unite the two interests between investors and workers to grow the national economy after it slumped due to the global crisis due to the COVID-19 pandemic. Hence, it is necessary to do research on the arrangement of Work Agreements according to the Job Creation Act. To describe these problems, a normative juridical legal research method was used with a descriptive type of research. The results of the analysis were basically the difference in the arrangement of the work agreement, more precisely in the work agreement for a certain time, in the job copyright law, there is a maximum period of accumulation of the term of the work agreement, which is 5 years and for a work agreement for a certain time, which is based on the completion of a job. It has a period until the completion of the work. It also allows for more than 5 different years from the previous arrangement.